Bach1 Inhibition Suppresses Osteoclastogenesis via Reduction of the Signaling via Reactive Oxygen Species by Reinforced Antioxidation - Wada, Satoshi; Kanzaki, Hiroyuki; Katsumata, Yuta; Yamaguchi, Yuuki; Narimiya, Tsuyoshi; Attucks, Otis C.; Nakamura, Yoshiki; Tomonari, Hiroshi (Frontiers in Cell and Developmental Biology, 2020)
Bone destructive diseases are common worldwide and are caused by dysregulation of osteoclast formation and activation. Receptor activator of nuclear factor-κB ligand (RANKL) is stimulated during osteoclastogenesis. This triggers reactive oxygen species (ROS), which has a key role in intracellular signaling as well exerting cytotoxicity. Cells have protective mechanisms against ROS, such as nuclear factor E2-related factor 2 (Nrf2), which controls the expression of many antioxidant enzyme genes. Conversely, BTB and CNC homology 1 (Bach1), a competitor for Nrf2, transcriptionally represses the expression of anti-oxidant enzymes. Previously, we demonstrated that RANKL induces Bach1 nuclear import and attenuates the expression of Nrf2-mediated antioxidant enzymes, thereby augmenting intracellular reactive oxygen species signaling and osteoclastogenesis. However, it remains unknown if Bach1 inhibitors exert an anti-osteoclastogenic effect. In this study, we hypothesized that Bach1 inhibition would inhibit osteoclastogenesis and bone destruction via attenuation of intracellular ROS signaling through antioxidant mechanisms. RAW 264.7 cells were used as osteoclast progenitor cells. Using flow cytometry, we found that Bach1 inhibitors attenuated RANKL-mediated intracellular ROS generation, which resulted in the inhibition of RANKL-mediated osteoclastogenesis. Local injection of a Bach1 inhibitor into the calvaria of male BALB/c mice resulted in attenuated bone destruction induced by lipopolysaccharide. In conclusion, we demonstrate that Bach1 inhibition inhibits RANKL-mediated osteoclastogenesis and bone destruction in mice by inducing the expression of Nrf2-mediated antioxidant enzymes that consequently decrease intracellular ROS levels. Our results suggest that Bach1 inhibitors have potential in inhibiting bone destruction in diseases such as periodontitis, rheumatoid arthritis and osteoporosis.